Classification of the fundamental frequency identification methods - Юдін, О. К.; Зюбіна, Р. В. (Science-based technologies, 2017)
A significant role in the formation of the voice characteristics of the information signals given to the speaker system represents a language group, which is responsible for basic voice parameters such as pitch frequency of the signal, information frames and properties frequency range, volume, frequency and rate of speech, intonation, etc. The main criteria features of voice were identified. The basic characteristics of audio signals generated by a person of a certain language group were analyzed. The methods and models to identify the fundamental frequency, which further gave the opportunity to determine the period of the fundamental tone were analyzed. In the current research, the determination of the fundamental frequency, there are problems such as the complexity of the implementation methods, and low probability of error in determination process; low resistance methods to external interference. Methods of determination of fundamental frequency with the plane of their implementation were classified.